Changes in the Etiologies of Liver Cancer in Upper Egypt over a Decade from 2010 to 2020: A Single Tertiary Care Center Study - Fouad, Yasser; Gaber, Yasmine; Alem, Shereen Abdel; Abdallah, Mohamed; Abd-Elsalam, Sherief M.; Nafady, Shaymaa; Attia, Dina; Eslam, Mohamed (South Asian Journal of Cancer, 2023)
The profile of liver diseases in Egypt is changing dramatically and viral hepatitis is declining, while the fatty liver disease is increasing dramatically. However, the impact of these changes on the profile of hepatocellular carcinoma (HCC) remains uncertain. Therefore, we determined the temporal trends in the etiologies of HCC in Egypt over a decade. We retrospectively analyzed data from consecutive patients who were diagnosed with HCC over 10 years (2010–2020) in a large center in Upper Egypt. Standard tests were utilized to diagnose hepatitis C virus (HCV) and hepatitis B virus. In the absence of other liver disorders, the presence of obesity, or diabetes in the absence of other risk factors, metabolic dysfunction-associated fatty liver disease (MAFLD) was diagnosed. A total of 1,368 HCC patients were included, in which 985 (72%) had HCV, 58 (4%) had hepatitis B virus, and 143 (10.5%) had MAFLD, 1 patient had hemochromatosis, 1 had autoimmune liver disease, and 180 (13%) patients were with unknown cause. The annual proportions of MAFLD-related HCC were increased significantly between 8.3% in 2010 and 20.6% in 2020 (p = 0.001), while HCV-related HCC declined from 84.8 to 66.7% (p = 0.001). Throughout the study period, there were significant increases in the age at diagnosis of HCC, the proportion of female patients, obesity, diabetes, and less severe liver dysfunction at diagnosis (p < 0.05 for all). With the decline of HCV, MAFLD is becoming a major cause of HCC in Egypt, which has increased substantially over the past 10 years. This study urges the creation of comprehensive action strategies to address this growing burden.
Keywords: HCC; Egypt; MAFLD; viral hepatitis; trends